The implication of Artificial Insemination Technology on Farmers’ Willingness to Adopt the Beef Cattle in Soppeng Regency - Bonewati, Yulia Irwina; Farid, Muhammad; Herni, Herni; Agustan, Agusta; Hamka, Hamka (Buletin Peternakan, 2024)
Artificial insemination is a widely adopted technique in the livestock industry to enhance breeding performance and improve the quality and quantity of cows. However, implementing this technology in Soppeng Regency is currently facing a challenge that has resulted in low pregnancy rates among cows. Therefore, it is imperative to conduct a comprehensive evaluation to identify the root cause of the unsatisfactory outcomes and find practical solutions to improve the success rate of artificial insemination in the region. This study aimed to implicate the factors influencing farmers' adoption of artificial insemination technology. It was carried out between July and September 2023 in Marioriawa, Lalabata, and Marioriwawo districts of Soppeng Regency, South Sulawesi Province. An explanatory study was used to implicate the factors that influenced adopting artificial insemination technology in farmers by involving 140 respondents and analyzed using binary logistic regression. The successful adoption of artificial insemination technology in beef cattle farmers in Soppeng Regency depends on various factors. While technical aspects and supporting infrastructure are critical, other factors, such as farmers' willingness to adopt the technology, proactive attitudes, and positive perceptions, also play a significant role in farmers’ decision-making. Additionally, regional accessibility, farming maintenance systems, and extension activities are crucial aspects to consider. Therefore, before implementing the technology, it is essential to pay special attention to these areas and provide appropriate interventions to ensure its success